Evaluation of load transfer mechanism under axial loads in a novel coupler of dual height rock bolts - Kumar, Ranjan; Mandal, Prabhat Kumar; Narayan, Ashish; Das, Arka Jyoti (International journal of mining science and technology, 2021)
The effective reinforcement of two or more overlying layers of mine openings in a single installation is usually done by coupling of two standard rock bolts mainly during the extraction of medium-thick coal seams. However, field observations show that the couplers of multiple bolts often degrade or break mostly at their connections. These types of failures can be avoided by strengthening the couplers of such multi-bolts assemblies. To achieve this, a novel threaded coupler system with an expansion shell was suggested in this paper. The newly designed coupler consists of a threaded tapered-plug-cum-connector with an expansion shell for connecting and tightening two standard rock bolts. An analytical model for evaluating the load distribution along the coupler subject to axial load was derived. Numerical analysis was performed to analyse the load transfer, deformation, and strains across the coupler including the factor of safety for the bolt-coupler-resin and bolt-coupler-expansion shell. The results validated the analytical model of the proposed coupler design, which provides better anchorage near the interface of the host rock mass. Thus, the developed coupler design would reduce the failures of the proposed coupler and stabilize laminated roof strata above the medium-thick coal seams in underground mines.